화물열차 사고에 의한 수질 오염 발생 시 초동조치에 관한 연구 - 최용환 (The Graduate School, Ajou University, 2024)
2007년 태안 해양오염 사고 이후로 해양오염 사고에 대한 경각심이 높아졌으며, 상수도원과 관광자원이 되는 하천의 오염 예방과 수질 보호도 못지않게 관심과 중요도가 높아지고 있다. 특히 우리나라의 한강은 생태학적 다양성이 높을 뿐 아니라 서울특별시와 경기도의 상수원으로 이용되어 그 가치가 높고, 한강의 수질 보호는 시민들의 건강을 위해 매우 중요한 의미가 있다. 여러 의미로 중요한 한강 위 철교를 통해 위험물을 포함한 각종 화물이 하루에 수 백 대의 화물열차가 운행하고 있어 철도에 의한 수질오염사고에 대한 위험성도 간과할 수 없다. 만약 한강을 지나는 철교 위에서 철도 사고가 발생한다면 인명 피해는 물론이고 화물 열차 등에 의한 수질 오염의 피해도 심각할 것으로 예상된다. 그러나 현재 한강과 같은 하천 위에서의 철도 사고 발생과 같이 하나의 사고로 복합적인 피해가 예상되는 사고와 관련해서는 각 기관별로 개별적인 대응체계가 있을 뿐 통합적인 종합 대응체계가 부족한 현실이다. 따라서 본 연구에서는 철교 위에서의 사고 상황을 가정하고 화물열차 사고 발생 시 시간에 따른 수질오염의 범위를 산정하고 이에 따른 타임라인 별 각 기관의 대응체계를 통합하여 종합적인 사고 대응체계를 마련하였다. 이를 통하여 사고로 인한 예상되는 피해를 최소화하고 나아가 본 연구에서 정립한 통합 사고대응 체계를 바탕으로 하나의 사고로 인해 다양한 범위에 피해를 미치는 유사한 사고에 대한 통합적 초동조치 체계를 수립하는데 도움이 되기를 기대할 수 있다.|Since the Taean maritime pollution accident in 2007, awareness of marine pollution accidents has increased, and interest and importance are increasing as well as the prevention of pollution and water protection of rivers that serve as water sources and tourism resources. In particular, Korea's Han River has high ecological diversity and is used as a water source in Seoul and Gyeonggi-do, so its value is high, and the protection of the water quality of the Han River is of great importance for the health of citizens. In many meanings, hundreds of freight trains, including dangerous goods, run a day through the important railway bridge over the Han River, so the risk of water pollution accidents by railroads cannot be overlooked. If a railroad accident occurs on a railroad bridge passing through the Han River, it is expected that not only human damage but also water pollution caused by freight trains will be serious. However, the reality is that each institution has an individual response system and lacks an integrated comprehensive response system for accidents that are expected to cause complex damage due to a single accident, such as a railroad accident on a river such as the Han River. Therefore, in this study, assuming an accident situation on a railroad bridge, the scope of water pollution over time was calculated in the event of a freight train accident, and a comprehensive accident response system was prepared by integrating each institution's response system for each timeline. This can be expected to minimize the expected damage caused by accidents and further help establish an integrated initial action system for similar accidents that damage various ranges due to a single accident based on the integrated accident response system established in this study.
학위논문(석사)--철도시스템학과,2024. 2
Keywords: 대응체계; 수질 오염; 초동조치; 화물열차 사고